Effects of distinct pollinators on the mating system and reproductive success in Incarvillea sinensis, an annual with large floral displays. (10th January 2018) - Ma, Yue; Yin, Ge; Gao, Jing; Luo, Yi-Bo; Bai, Wei-Ning
Abstract: Aims: Most flowering plants engage in mutualisms with animals to move pollen between individuals, and it is expected that pollinators play an essential role in the evolution of selfing, yet few studies have determined how distinct pollinator types affect a plant's mating system and reproductive success differentially. We investigated the effect of two different pollinators on the reproductive success of Incarvillea sinensis, an annual with showy, insect-pollinated, one-day flowers. Methods: We marked flowers after a single visit from both pollinator species ( Bombus patagiatus and Amegilla quadrifasciata ) and calculated the number of pollen grains deposited on the stigma and pollen left in the anthers, the fruit and seed set, the outcrossing rate and the correlations of paternity. Important Findings: There was no significant difference in the number of pollen grains deposited on the stigma, or in the seed and fruit set between the two pollinators in both years. The mean number of pollen grains removed by B. patagiatus was significantly higher than that removed by A. quadrifasciata . The outcrossing rate of flowers pollinated by B. patagiatus was significantly higher than that of flowers pollinated by A. quadrifasciata . The correlation of paternity of flowers pollinated by B. patagiatus was significantly lower than that of flowers pollinated by A. quadrifasciata . For I. sinensis, B. patagiatus may exhibit larger pollen wastage, thus reducing the male reproductive success of the plant, but it causes higher female reproductive success because of its higher outcrossing rate and the lower correlation of paternity. Our findings highlighted that different animal pollinators could indeed cause differential mating systems and reproductive success.